Evaluación de las metodologías del control interno en las cooperativas de ahorro y crédito interandina y sierra centro agencias del cantón Salcedo de la provincia de Cotopaxi - Barreros Peralvo, Katherin Vanessa (2017)
In the following project research it aims to make an evaluation of internal control methodologies in Interandina and Sierra Centro credit unions in canton Salcedo in the Cotopaxi province. Its purpose was found weaknesses and bankrupt exist in each area at the moment to develop activities. For this was necessary to make a field work, through descriptive research which allows to describe activities, financial stages and staff that develop in the different sections, applying interviews to the managers, accountants and bosses of each credit union. It was developed a survey of internal control, functions descriptions. Process and design of flowchart which were applied to the control system components are: management, risk evaluators, control activities, information, communication and monitoring to get good results and achieving a benchmarking besides it could determine what’s going on with credit unions, this research will benefit to partners, investors, employees and the community through enhancing financial process, personal staff allow it to take decisions with that achieve the goals set.